2007
DOI: 10.1002/chin.200733147
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Highly Stereoselective Synthesis of 2,3‐Disubstituted 3H‐Quinazoline‐4‐one Derivatives.

Abstract: A Novel Highly Stereoselective Synthesis of 2,3-Disubstituted 3H-Quinazoline-4-one Derivatives. -The approach includes the Mumm reaction of imidoyl chlorides with α-amino acids followed by reductive cyclization as key steps. -(ZHICHKIN*, P.; KESICKI, E.; TREIBERG, J.; BOURDON, L.; RONSHEIM, M.; OOI, H. C.; WHITE, S.; JUDKINS, A.; FAIRFAX, D.; Org. Lett. 9 (2007) 7, 1415-1418; Albany Mol. Res., Inc., Albany, NY 12212, USA; Eng.) -R. Steudel 33-147

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, the development of the efficient synthetic methods for various quinazolinones has attracted great interest from synthetic chemistry. Most of the reported methods are about the synthesis of quinazoline-4-ones [10][11][12][13][14][15] and quinazoline-2,4-(1H,3H)-diones. [16][17][18][19] Only a two-step reaction has been reported for the synthesis of quinazoline-5-ones 8 although octahydroquinazoline-5-ones, for example III in 3…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of the efficient synthetic methods for various quinazolinones has attracted great interest from synthetic chemistry. Most of the reported methods are about the synthesis of quinazoline-4-ones [10][11][12][13][14][15] and quinazoline-2,4-(1H,3H)-diones. [16][17][18][19] Only a two-step reaction has been reported for the synthesis of quinazoline-5-ones 8 although octahydroquinazoline-5-ones, for example III in 3…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The benzamide moiety is found in a wide range of biologically active molecules and substituted benzamides have been used as insecticides, antiviral, and anti-inflammatory agents. [21][22][23][24][25] These compounds with variability in conformation are influenced by both electronic and structural effects. 26,27 A systematic study on halogen substituted benzamide has revealed that strong N-H• • •O=C interactions largely remain preserved in…”
Section: Introductionmentioning
confidence: 99%